2016
DOI: 10.1007/s13178-016-0226-0
|View full text |Cite
|
Sign up to set email alerts
|

Minimization of Male Suffering: Social Perception of Victims and Perpetrators of Opposite-Sex Sexual Coercion

Abstract: Studies show equal impact of sexual harassment (SH) on men and women, whereas lay perceptions are that women suffer more. We identify the phenomenon of minimization of male suffering (MMS), which occurs when people assume that SH has less effect on men’s well-being and which results in the perpetrators of SH on men being evaluated less harshly. To verify whether these effects occur, we conducted two studies in which we presented stories describing acts of sexual coercion (SC, study 1) and SC or financial coerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
4
0
1
Order By: Relevance
“…Although there is limited research comparing opinions of male and female victims, previous research has found that DVA against males is viewed as less obvious and more normalised than DVA against females (Bates et al, 2018) which may explain kinder responses towards female victims. This belief also extends to sexual harassment, as participants minimised male victims' experiences and perceived them as sustaining less severe consequences (Studzinska & Hilton, 2016). This finding may also be explained through drawing on the wider DVA literature considering perpetrators.…”
Section: Discussionmentioning
confidence: 85%
“…Although there is limited research comparing opinions of male and female victims, previous research has found that DVA against males is viewed as less obvious and more normalised than DVA against females (Bates et al, 2018) which may explain kinder responses towards female victims. This belief also extends to sexual harassment, as participants minimised male victims' experiences and perceived them as sustaining less severe consequences (Studzinska & Hilton, 2016). This finding may also be explained through drawing on the wider DVA literature considering perpetrators.…”
Section: Discussionmentioning
confidence: 85%
“…Data from the Pew Research Center (2018) shows that 27% of U.S. males report having been sexually harassed. And while the self-reported suffering of men who have been sexually assaulted or harassed has been shown to be equal to that of women, men are generally perceived by others as suffering less (Studzinska & Hilton, 2017). When it comes to speaking out about their experiences, therefore, fear of ostracization may be as much or more of a barrier for men as for women.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon has been researched in relation to perceptions of working parents (Cuddy et al, 2004;Fuegen & Endicott, 2010;Gaunt, 2013;Rudman & Mescher, 2013), job applications (Phelan et al, 2008;Rudman & Glick, 1999), leadership abilities and skills (Eagly & Karau, 2002), judicial decision-making (Pozzulo et al, 2009;Miller, 2018), or feminine-and masculinelooking robots (Eyssel & Hegel, 2012), among others. It has also been demonstrated in the context of immoral behaviors, such as sexual assault (Davies & Rogers, 2006;Fromuth et al, 2001;Gakhal & Brown, 2011), child sexual abuse (Tozdan et al, 2019;Zack et al, 2018), intimate partner violence (Cormier & Woodworth, 2008;Dutton & White, 2013;Hamby & Jackson, 2010;Jackson Harris & Cook, 1994;Seelau & Seelau, 2003;Seelau & Seelau, 2005), and-as described above-sexual harassment (Bursik & Gefter, 2011;Pina & Gannon, 2010;Studzinska & Hilton, 2017). Frequently, for opposite-gender cases, female victims were viewed as suffering more than male victims, and male perpetrators were regarded as deserving more punishment or being more responsible than female perpetrators.…”
Section: Theory Development and Hypothesesmentioning
confidence: 94%